Clinical impact of FFR‐guided PCI compared to angio‐guided PCI from the France PCI registry. Issue 1 (11th May 2022) - Adjedj, Julien; Morelle, Jean‐Francois; Saint Etienne, Christophe; Fichaux, Olivier; Marcollet, Pierre; Decomis, Marie Pascale; Motreff, Pascal; Chassaing, Stephane; Koning, Rene; Range, Gregoire; ,
Abstract: Objectives: We sought to compare, in a national French registry (FrancePCI), the clinical impact of fractional flow reserve (FFR)‐guided percutaneous coronary intervention (PCI) compared with angio‐guided PCI at 1 year. Background: FFR has become the invasive gold standard to quantify myocardial ischemia generated by a coronary stenosis in patients with chronic coronary syndrome, but in clinical practice it is still underutilised to guide PCI compared to angiography (angio). Methods: We extracted from the FrancePCI database all chronic coronary syndrome patients treated with PCI for coronary stenosis <90% between 2014 and 2019. Our composite clinical endpoint was the rate of major adverse clinical events (MACE). Results: Fourteen thousand three hundred eighty‐four patients with 1‐year clinical follow‐up were included. Among them, 13, 125 had angio‐guided PCI (91%) and 1259 (9%) had FFR‐guided PCI. We observed a significantly higher rate of MACE in the angio‐guided group versus the FFR‐guided group: 1478 (11.3%) versus 100 (7.9%) ( p < 0.0001), respectively, with hazard ratio (HR) of 1.440, 95% confidence interval (CI) [1.211−1.713] ( p = 0.0004). This result was driven by the higher occurrence of death in the angio‐guided group versus the FFR‐guided‐group: 506 (3.9%) versus 17 (1.4%) ( p < 0.0001), respectively, with HR of 2.845, 95% CI [2.099−3.856] ( p < 0.0001). After adjustment for potential confounding factors, HRs were 1.287, 95% CI [1.028−1.613] ( p = 0.028) for MACE and 2.527, 95% CI [1.452−4.399] ( p = 0.001) for death. No significant differences between angio‐guided PCI and FFR‐guided PCI were observed for other clinical endpoints. Conclusions: FFR‐guided PCI improves outcome at 1 year compared to angio‐guided PCI with a reduction of 64% of death.